Synthesis of spirooxindoles with three component reaction between β-ketoesters, malononitrile and isatin derivatives in the presence of Alum.SiO2 nanoparticles as a new nano catalyst - Rohi, Marziyeh; Sadeghi, Bahareh; Moslemin, Mohamadhosaine (Ciência e Natura, 2015)
In this reseaech, some of the spirooxindole derivaties were prepared via β-ketoesters, malonoitrile and isatin derivatives in the presenceAlum.SiO2 NPs as an effective, recyclable and inexpensive catalyst. The products were identified by IR, 1HNMR, 13C NMR spectr a, andmelting point. The size of nanoparticles characterized by SEM and TEM techniques. A novel multicomponent synthesis of a series ofspirooxindol derivatives is described. The procedures was carried out applying Alum/SiO2 supported on NPS as the novel cataly st givingrise to high to excellent yielded synthetic route of spirooxindol compounds. The major advantages of this protocol are short reaction time,good yields , simple procedure work up as well as friendly synthesis. In this work, some of the spirooxindole derivaties wer e prepared via β-ketoesters, malononitrile and isatin derivatives in the presence Alum.SiO2 NPs as an effective, recyclable and inexpensive catalyst. Theproducts were identified by IR,1HNMR,13CNMR spectra, and melting point. The size of nanoparticles characterized by SEM and TEMtechniques.(scheme 1)